Evaluation of the Usefulness of Consensus Definitions of Sarcopenia in Older Men: Results from the Observational Osteoporotic Fractures in Men Cohort Study. Issue 11 (27th October 2015) - Cawthon, Peggy M.; Blackwell, Terri L.; Cauley, Jane; Kado, Deborah M.; Barrett‐Connor, Elizabeth; Lee, Christine G.; Hoffman, Andrew R.; Nevitt, Michael; Stefanick, Marcia L.; Lane, Nancy E.; Ensrud, Kristine E.; Cummings, Steven R.; et al.
Abstract : Objective: To evaluate the associations between definitions of sarcopenia and clinical outcomes and the ability of the definitions to discriminate those with a high likelihood of having these outcomes from those with a low likelihood. Design: Osteoporotic Fractures in Men Study. Setting: Six clinical centers. Participants: Community‐dwelling men aged 65 and older (N = 5, 934). Measurements: Sarcopenia definitions from the International Working Group, European Working Group on Sarcopenia in Older Persons, Foundation for the National Institutes of Health Sarcopenia Project, Baumgartner, and Newman were evaluated. Recurrent falls were defined as two or more self‐reported falls in the year after baseline (n = 694, 11.9%). Incident hip fractures (n = 207, 3.5%) and deaths (n = 2, 003, 34.1%) were confirmed according to central review of medical records over 9.8 years. Self‐reported functional limitations were assessed at baseline and 4.6 years later. Logistic regression or proportional hazards models were used to estimate associations between sarcopenia and falls, hip fractures, and death. The discriminative ability of the sarcopenia definitions (vs reference models) for these outcomes was evaluated using area under the receiver operating characteristic curve or C‐statistics. Referent models included age alone for falls, functional limitations and mortality, and age and bone mineral density for hip fractures. Results: The association between sarcopenia according to the various definitions and risk of falls, functional limitations, and hip fractures was variable; all definitions were associated with greater risk of death, but none of the definitions materially changed discrimination based on the AUC and C‐statistic when compared with reference models (change ≤1% in all models). Conclusion: Sarcopenia definitions as currently constructed did not consistently improve prediction of clinical outcomes in relatively healthy older men.